Transformers one [videorecording (DVD)] - Pearson, Eric, 1980-; Barrer, Andrew, 1984-; Ferrari, Gabriel (Screenwriter); Tyler, Brian (Composer) (Paramount, 2024)
The untold origin story of Optimus Prime and Megatron. Known as sworn enemies, once they were friends bonded like brothers who changed the fate of Cybertron forever. The first-ever fully CG-animated Transformers movie.